Incorporating Bicycles into Urban Mobility: An Opportunity for Sustainable Development - Lopez-Escolano, Carlos; Campos, Angel Pueyo; Pardos, Sergio Valdivielso; Nedeliakova, Eva; Stefancova, Vladimira (Communications - Scientific letters of the University of Zilina, 2017)
This paper addresses the new role of bicycles as a mode of sustainable urban transport in several cities, after decades of being seen as a minor means of transport. Socio-economic changes over the last few decades and demands from a much more aware public are facilitating the re-incorporation of bicycles into areas not only where they are normally found, such as northern European countries, but also into less usual places, like Spain. In this context, this research aims to assess how much access the public has to various cycling infrastructures, such as bicycle lanes or bike-sharing stations. It also delves into how urban planning and management have made it possible to bicycles in the urban scene, also the main challenges and difficulties to be overcome to make full integration. The analysis includes drawing up themed maps to assess accessibility in the city of Zaragoza in Spain, one of the examples of a change in urban mobility towards a more sustainable system.